Desain Smart Body Vest Untuk Meminimalisir Kecelakaan Kerja Menuju Indonesia Zero Accident - Mohammad Iskandar Nur Fahmi; Muhammad Bagus Panuntun; Andayani Yuwana Sari; Febri Liantoni (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2020)
The construction sector plays an important role in a country's economy. This is because construction projects such as the construction of buildings, roads, bridges and other infrastructure are one of the benchmarks of economic progress and civilization of a country. Work accidents on construction projects can cause work to stop and result in financial losses and decreased work productivity. According to the Minister of Manpower in 2018 the number of work accidents has increased from the previous year even from the data of the Central Statistics Agency stating that the majority of construction workers are junior high school graduates and below. This is one of the factors causing the increase in occupational accidents in the construction sector. Losses from work accidents are also included in workers' losses, damage to equipment and materials wasted due to work accidents. Occupational health and safety (K3) risk control is very important as a preventive effort to prevent a bigger event. One such control is the use of Personal Protective Equipment (PPE) or more commonly called personal protective equipment (PPE). The existence of PPE is important for workers to minimize the impact of accidents so that each company is obliged to use PPE. This study aims to minimize the number of work accidents in Indonesia, especially in the construction sector. The method used in making the body vest is the addition of an airbag by applying the fall detection algorithm to the K-Nearest Neighbor (KNN), which is to calculate the Euclidean distance which is the distance between the sample and training data and then determine the k nearest data from the sample so that the sample can be classified on the sensor and microcontroller. The way it works is when a collision or a hard collision occurs, workers will generally be thrown or dropped then there will be a change in the acceleration of the position of the body wearing a body vest. The change in acceleration triggers the development of airbags on the body vest. This is expected to reduce injuries to vital organs in the worker's body.